2022
DOI: 10.3390/jcm11051284
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Relieves Testicular Ischemia-Reperfusion Injury—Immunohistochemical and Biochemical Analyses

Abstract: Testicular torsion potentially leads to acute scrotum and testicle loss, and requires prompt surgical intervention to restore testicular blood flow, despite the paradoxical negative effect of reperfusion. While no drug is yet approved for this condition, antioxidants are promising candidates. This study aimed to determine astaxanthin’s (ASX), a potent antioxidant, effect on rat testicular torsion−detorsion injury. Thirty-two prepubertal male Fischer rats were divided into four groups. Group 1 underwent sham su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Many studies examining the effects of different substances in counteracting the different mechanisms involved in testicular I/R damage were performed, testing the role of vitamin C [ 39 ], the melanocortin analog [Nle(4),D-Phe(7)]α-melanocyte-stimulating hormone [ 40 ], α-lipoic acid [ 41 ], ghrelin [ 42 ], melatonin [ 43 ], astaxanthin [ 7 ], and relaxin [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies examining the effects of different substances in counteracting the different mechanisms involved in testicular I/R damage were performed, testing the role of vitamin C [ 39 ], the melanocortin analog [Nle(4),D-Phe(7)]α-melanocyte-stimulating hormone [ 40 ], α-lipoic acid [ 41 ], ghrelin [ 42 ], melatonin [ 43 ], astaxanthin [ 7 ], and relaxin [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, testis I/R can be obtained with different procedures. In fact, it can be induced by torsion of the spermatic cord, followed by detorsion, both procedures lasting different lengths of time [ 6 , 7 ]. Another procedure is the use of a small microvascular clump placed on the spermatic cord in order to block the spermatic vessels; then, the clump is removed, allowing the reperfusion of the testis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular torsion is a critical urologic disease caused by winding of the spermatic cord around the testis ( Guazzone and Lustig, 2023 ; Lacy et al, 2023 ). The incidence of testicular torsion is 1 in 4,000 in male individuals younger than 25 years of age, whereas the prevalence of testicular torsion out of all acute scrotal conditions is 25%–50% ( Baskovic et al, 2022 ). Despite timely detorsion, testicular atrophy may still occur in 9.1%–73.3% of patients in long-term follow up, seriously affecting their spermatogenic functions ( Wei and Huang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies demonstrated the benefits of astaxanthin on testicular ischemia/reperfusion. In these studies, the protective effects of a single dose of astaxanthin administered during or after detorsion on testicular tissue and its protective effects against oxidative damage and histopathological changes in testicular torsion were investigated [4,12]. Although astaxanthin has been shown to play a protective role against testicular ischemia/reperfusion injury, related metabolic pathways are still unknown.…”
Section: Introductionmentioning
confidence: 99%